The Economic Life of Basra City, as Described in the Books of Geographers and Muslim Travelers up to the year (334 AH/945 AD) - Kahit Faisal , Lect . Dr. Yusra (Basra studies journal, 2026)
The Economic situation in the city of Basra developed after the establishment of the Arab Islamic conquests in it, which led to attracting a large number of people to it, due to the important and vital geographical location of the city, as it overlooks the head of the Arabian Gulf, which made it a link between the Far East (India and China) and East Africa on one side and the Arabian Peninsula on the other. The city of Basra is one of the important places in Iraq throughout history, due to the great importance it has formed in all economic aspects of agriculture, industry, and trade . Basra is one of the most prominent cities in Iraq, possessing the elements of economic development throughout history. The writings of Arab geographers and travelers are often relied upon to fill gaps in any subject of historical studies, in addition to travelogues which are a rich source of information for historical writing.